Investigation on research innovation ability and training demand of clinical nursing staff (临床护理人员科研创新能力及培训需求现况调查) - YAN Xin (闫欣); QI Lixia (祁丽霞); WANG Zheng (王征); WEI Rui (卫蕊); LI Bin (李斌) (中西医结合护理)
Objective To understand the scientific research innovation ability and training needs of clinical nursing staff at all levels of hospitals, so as to provide a reliable basis for the development of training programs to improve the scientific research ability and innovation level of clinical nursing staff. Methods Convenience sampling method was used to select a total of 1289 clinical nurses from 15 hospitals in the region as the research objects, and the questionnaire was used to investigate the scientific research innovation ability and training needs of clinical nursing staff. Results The average score of innovation ability of nursing staff was 2. 91. The average score of scientific research ability was 2. 78. There was an urgent need for the training of patent innovation, scientific research and other stages; Lack of confidence in the competence of scientific research and innovation; Sufficient understanding of the necessity of carrying out research and innovation ability training; willingness of participating in various forms of nursing research training; Most nurses believed that scientific training and learning is for self-improvement. Conclusion At present, the level of scientific research innovation of clinical nursing staff is low, and there is a strong demand for training in scientific research innovation. Therefore, strengthening the training of scientific research innovation of nursing staff at all stages in the future will be of great help to improve the level of scientific research innovation of nursing staff. (目的 了解各级医院临床护理人员科研创新能力及培训需求, 为制定提升临床护理人员科研能力及创新水平的培训方案提供依据。方法 采用便利抽样法选取本地区15所医院共1289名临床护士作为调研对象, 采用临床护理人员科研创新能力及培训需求调查问卷进行调查。结果 护理人员的创新能力平均得分2. 91分; 科研能力平均得分2. 78分; 对关于专利创新、科研的等各阶段的培训需求均有迫切需求; 对胜任科研创新工作的自信度缺乏; 对开展科研创新能力培训工作必要性的认识充足; 希望参加各种形式的护理科研培训; 多数护理人员认为进行科研培训与学习是为了自我提高。结论 现阶段, 临床护理人员的科研创新水平偏低, 对科研创新等方面的培训需求强烈, 因此, 在今后加强护理人员科研创新各阶段的培训, 对提高护理人员科研创新水平有很大帮助。)